Analisis Pengaruh Produk Domestik Regional Bruto (PDRB) Terhadap Kemiskinan di Kabupaten Bone Bolango - Andres Akaseh; Muhdar H.M; Andi Mardiana (Al-Buhuts, 2021)
Gross Regional Domestic Product (GRDP) is a factor that shows the economic condition of a region in a certain period, either on the basis of current prices or on the basis of constant prices. Gross Regional Domestic Product (GDP) at current prices shows the added value of goods and services calculated using prices per current year, while Gross Regional Domestic Product (GRDP) at constant prices shows the added value of goods and services calculated using prices valid for one year as the base year. The purpose of this study was to determine the effect of Gross Regional Domestic Product (GRDP) on poverty levels in Bone Bolango Regency. This research is a quantitative research. The type of data used is secondary data originating from the publication of the Central Statistics Agency with time series data for the last 10 years, namely from 2010 - 2019. The data analysis used is simple linear regression analysis. The data is processed using SPSS. The results of the study note that the Gross Regional Domestic Product (GRDP) has no effect on the poverty level in Bone Bolango Regency